A Look at the Design of Lua. - IERUSALIMSCHY, ROBERTO; DE FIGUEIREDO, LUIZ HENRIQUE; CELES, WALDEMAR (Communications of the ACM, 2018)
The article reports on potential uses for the Brazilian scripting language Lua. It mentions the simplicity and portability of the language, the tables and functions that are part of Lua as well as their capabilities, and the coroutines that can be used in operations.